Multiloop Parallelisation Using Unrolling and Fission. (17th January 2010) - Lam, Yuet Ming; Coutinho, José Gabriel F.; Ho, Chun Hok; Leong, Philip Heng Wai; Luk, Wayne
Abstract : A technique for parallelising multiple loops in a heterogeneous computing system is presented. Loops are first unrolled and then broken up into multiple tasks which are mapped to reconfigurable hardware. A performance-driven optimisation is applied to find the best unrolling factor for each loop under hardware size constraints. The approach is demonstrated using three applications: speech recognition, image processing, and the N-Body problem. Experimental results show that a maximum speedup of 34 is achieved on a 274 MHz FPGA for the N-Body over a 2.6 GHz microprocessor, which is 4.1 times higher than that of an approach without unrolling.